Risk factors and frequency of COVID-19 among healthcare workers at a tertiary care centre in India: a case–control study. (24th March 2021) - Dev, Nishanth; Meena, Ramesh Chand; Gupta, D K; Gupta, Nitesh; Sankar, Jhuma
Abstract: Background: There is a paucity of data on risk factors for infection among healthcare workers (HCWs) from India. Our objective was to evaluate the risk factors and frequency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among HCWs. Methods: We conducted this retrospective case–control study of 3100 HCWs between May and July 2020. HCWs positive for SARS-CoV-2 infection were the cases (n=506) and those negative for SARS-CoV-2 were the controls (n=253). Univariate analysis was followed by multivariate analysis of key demographic, clinical and infection control variables. Results: SARS-CoV-2 infection was found in 16.32% of HCWs. Nearly 45% of infected HCWs were asymptomatic. The proportions of sanitation workers (24% vs 8%; p<0.0001) and technicians (10% vs 4%; p=0.0002) were higher and that of doctors was lower among cases as compared with controls (23% vs 43%; p<0.0001). On univariate analysis, the type of HCW, smoking, lack of training, inadequate personal protective equipment (PPE) use and taking no or fewer doses of hydroxychloroquine (HCQ) were found to be significant. On multivariate analysis, the type of HCW (risk ratio [RR] 1.67 [95% confidence interval CI 1.34 to 2.08], p<0.0001), inappropriate PPE use (RR 0.63 [95% CI 0.44 to 0.89], p=0.01) and taking fewer doses of HCQ (RR 0.92 [95% CI 0.86 to 0.99], p=0.03) were significant. Conclusions: The frequency of SARS-CoV-2 infection was 16% among HCWs. Being a sanitation worker, inappropriate PPE use and lack of HCQ prophylaxis predisposed HCWs to SARS-CoV-2 infection.